The Order to Cash Process’s Digitalization Impact on Logistics Processes in Manufacturing Companies - Adam KOLINSKI; Karolina KOLINSKA; Jozef FRAS (Communications of International Proceedings, 2021)
Background: The primary goal of processes digitalization is the information integration of business partners in the supply chain, which directly affects the sustainability of the supply chain, where the manufacturing company plays a key role. Digitalization improves the environmental performance of the processes by using the paperless concept (reduction of paper documents), but above all, the optimization of logistics processes by reducing delivery errors (material and finished products), reducing the lead time of logistics processes and thus reducing costs for manufacturing companies in the supply chain. The aim of the article is to present a concept of using the order to cash process digitalization, taking into account the different role of manufacturing companies in this process. Methods: The results of research conducted in the years 2018-2020 within the framework of research and development projects and literature research, show that the basic assumptions of the order to cash process digitalization, carried out by manufacturing companies, are not used to a sufficient degree. On their basis, a selection and comparison of factors influencing directly the possibility of the order to cash process digitalization was made in a comprehensive way, taking into account the specificity of different types of business partners in supply chains. Results: The results of the conducted research on the possibility of digitalization of processes are proposals of models of order to cash solution application, supported by business practice research in the form of surveys and expert opinions. The analysis of the application of the order to cash solution, despite numerous literary references, is still ambiguously defined. This makes it difficult to use it in the business practice of companies and to identify the economic and ecological benefits of the application. Conclusions: This article focuses on the presentation of solutions dedicated to particular models of the order to cash solution. The direction of further research should be an attempt to identify measurable environmental and ecological benefits from the use of this solution in business practice.
Keywords: Order to Cash; Supply Chain Digitization; Information Efficiency.